Catalysis for fine and specialty chemicals - Joshi, S. S.; Bhatnagar, A.; Ranade, V. V. (Industrial catalytic processes for fine and specialty chemicals, 2016)
The fine and specialty chemical industry is extremely diverse, encompassing pharmaceuticals, dyestuffs, food additives, agrochemicals, polymer additives, flavors and fragrances, various chemical intermediates, etc. Fine and specialty chemicals have been around for more than 100 years and they are produced with the aim of either being used as is or in the form of additives/formulations. These organic chemicals are generally manufactured in batch or semibatch processes. Most of these generally involve multistep processes and often generate significant by-products/effluents per kg of useful products. Catalysis can be effectively used to reduce such waste generation and to minimize consumption of raw materials. In this chapter, we present various applications of homogeneous, as well as heterogeneous catalysis and catalytic processes, which are particularly relevant to fine and specialty chemicals